Smelling multiple sclerosis: Different qualities of olfactory function reflect either inflammatory activity or neurodegeneration. (January 2020) - Bsteh, Gabriel; Berek, Klaus; Hegen, Harald; Teuchner, Barbara; Auer, Michael; Wurth, Sebastian; Di Pauli, Franziska; Deisenhammer, Florian; Berger, Thomas
Background: Peripapillary retinal nerve fiber layer (pRNFL) thickness and olfactory function are both emerging biomarkers in multiple sclerosis (MS). Impairment of odor identification and discrimination is an irreversible feature of more advanced MS suggested to be associated with neurodegeneration, while olfactory threshold is a transient feature of early, active MS possibly associated with short-term inflammatory disease activity. Objective: The aim of this study was to validate the association of olfactory (dys)function and parameters of MS disease course in a large cohort of MS patients and to correlate olfactory function with pRNFL thickness as a surrogate biomarker of neurodegeneration. Methods: In a cross-sectional design, olfactory function was assessed using the Sniffin' Sticks test, which quantifies three different qualities of olfactory function (threshold, discrimination, and identification). pRNFL thickness was measured by spectral-domain optical coherence tomography (OCT). Results were correlated with age, sex, disease duration, relapses, Expanded Disability Status Scale (EDSS), cognitive function, depression, smoking, and pRNFL thickness by multivariable linear regression models. Results: We included 260 MS patients (mean age of 35.9 years, 68.7% female). Olfactory threshold correlated significantly with number of relapses in the year prior to assessment and shorter disease duration. Odor discrimination, identification, and their sum score were significantly correlated with longer disease duration, higher EDSS, and reduced cognitive function. pRNFL thickness was associated with identification and discrimination, but not with threshold. Conclusion: Olfactory threshold is a marker of short-term inflammatory relapse activity unrelated to parameters of neurodegeneration, while odor identification and discrimination are markers of neurodegeneration mostly independent of relapse activity. Assessment of olfactory function provides an opportunity to stratify MS patients with regard to inflammation and neurodegeneration.